Highlighting the History of Astronomy in the Asia-Pacific Region Proceedings of the ICOA-6 Conference - Orchiston, Wayne; Nakamura, Tsuko; Strom, Richard G.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
This book provides readers with the results of recent research from some of the world's leading historians of astronomy on aspects of Arabic, Australian, Chinese, Japanese, and North and South American astronomy and astrophysics. It contains peer-reviewed papers gathered from the International Conferences on Oriental Astronomy 6 (ICO-6) with the chosen theme of "Highlighting the History of Astronomy in the Asia-Pacific Region." Of particular note are the sections on Arabic astronomy, Asian applied astronomy and the history of Australian radio astronomy, and the chapter on Peruvian astronomy. This title is a valuable complement for those with research interests in applied historical astronomy; archaeoastronomy; calendars, manuscripts, and star charts; historical instruments and observatories, and the history of radio astronomy.
Contents -- Foreword -- Participants -- Conference Program -- Part I: Applied Historical Astronomy -- Paper (Stephenson Eclipses) -- Paper(Tanikama et al.) -- Paper (Nha II-Seong Eclipse) -- Paper (Strom) -- Part II: Archaeoastronomy -- Paper (Vahia) -- Paper (Gullberg and Malville) -- Part III: Astronomers, Books, Manuscripts, and Star Charts -- Paper (Hafex et al.) -- Paper (Soma and Tanikawa) -- Paper (Ohashi) -- Paper (Yosida and Nakamura) -- Paper (Nah II-Seong Planisphere) -- Paper (Stephenson Korean MS) -- Part IV: Nineteenth Century Transits of Venus and Solar Eclipses -- Paper (Cottam ToV) -- Paper (Pearson et al.) -- Paper (Solar Eclipses) -- Part V: The History of Australian Radio Astronomy -- Paper (Wendt et al. Potts Hills) -- Paper (Wendt et al. Murraybank) -- Paper (Stewart et al. Wild) -- Paper (Wendt Wild and H-line) -- Paper (Wendt et al. Christiansen) -- Stewart (Retrospective).
Keywords: Astronomy; Astrophysics; History; Archaeology; Astronomy, Astrophysics and Cosmology; History of Science; Archaeology